SYNTHESIS OF MERCAPTOETHYL OLEATE - Aria Kusumah, Adriansyah
Polyvinyl chloride is the second most widely used polymer in the world. PVC has a global consumption rate of 56 million tons in 2022 and is expected to increase by 3.2% until 2024. Although PVC is widely used due to its thermoplastic properties, it has a weakness in its mechanical strength, which can be thermally degraded. Therefore, thermal stabilizers need to be added to PVC manufacturing. One of the commonly used thermal stabilizers is organotin thermal stabilizer. Organotin thermal stabilizers are produced through two stages, namely the synthesis of reverse esters from fatty acids and mercaptoethanol and the reaction between reverse esters and methyl tinchloride. The reverse ester synthesis from carboxylic acid and mercaptoethanol is an equilibrium reaction. The by-product water must be removed to shift the reaction towards the product. Water is removed through vacuum evaporation method. The pressure is decreased gradually to prevent mercaptoethanol from being vaporized. The vacuum rate and pressure drop step size are thought to affect the synthesis performance. This study aims to examine the effect of vacuum rate and pressure drop step size on the synthesis of mercaptoethyl oleate. This study uses oleic acid as carboxylic acid so that the reverse ester synthesized is called mercaptoethyl oleate. The synthesis was carried out in a partially jacketed glass reactor. The varied vacuum rates were 1.67 and 0.83 torr/min, while the varied pressure drop steps were 25 and 50 torr. The catalyst used in this study was pTSA. During the reaction, the temperature was maintained at 70°C. The synthesis performance was measured in terms of sulfhydryl content correlated with product purity, reactant residual acid number, and product yield. The results showed that the vacuum rate had a significant effect on the acid number, sulhydryl content, and product yield. On the other hand, the amount of pressure drop did not significantly affect the acid number, sulfhydryl content, and product yield. Based on FTIR analysis, all experimental variations were in agreement with the characteristic functional groups of mercaptoethyl oleate.